Experimental study and passive control of the bistable dynamics of the three-dimensional air-wake flow of a finite-width double backward-facing step - Mallat, B.; Pastur, L.R. (Journal of wind engineering and industrial aerodynamics, 2021)
Inspired by the study of Rao et al. (2019), the aerodynamics of a simplified frigate is investigated experimentally. The natural wake flow dynamics is shown to be bi-stable at zero yaw angles, at both the rear of the ship superstructure and the stern. The bi-stable dynamics is strongly weakened at the stern when the ship is lifted off the ground in the free-stream. Perimetric cavities of sufficient depth at the rear of the superstructure are able to suppress the bi-stable dynamics and to symmetrize the air-wake flow at both the superstructure and the stern. The base pressure increases with the cavity depth while the drag force slightly decreases. Our study experimentally confirms that perimetric rear cavities offer efficient devices for passive flow control strategies of the aerodynamic air-wake flow of bodies of complex geometries subject to bi-stable dynamics. •Experimental characterization of frigate wake bi-stable dynamics.•Frigate wake bi-stability suppressed by adding flaps at the superstructure.•Our findings could have implications for industrial aerodynamics.